Analiza in interpretacija prostora v literarnem besedilu - Tihomirović, Zoran (Slavistična revija, 2020)
This article analyzes the use of space and spatial categories as methodological tools in the analysis and interpretation of literary texts. Tendencies in spatial analysis are presented in four categories: the use of "spatial" terms within literary studies, space as a genre determinant, space as a narrative device, and the phenomenology of space. Emphasis will be placed upon a narratological approach towards space, the "implication" of space in literature, and the methodological possibilities and relevance of spatial analysis in literary studies.
Keywords: interpretacija prostora; kronotop; literarno besedilo; naratologija; perspektiva; prostorski obrat